A feasibility study on the establishment of an institutional archive in preservation of Fe Del Mundo Medical Center's history - Sio, Kendrik Philipp S.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study evaluated the feasibility of establishing an institutional archive in Fe Del Mundo Medical Center (FDMMC) based on the factors of market, technical, and financial feasibility.

The evaluation was done using an interview guide. Respondents of the study were the heads of the Business Development and Marketing Department and the administrative coordinator of the Office of the General Manager of FDMMC.

The results showed the feasibility of establishing an archive in Fe Del Mundo Medical Center. The study conveyed that FDMMC has a rich and varied collection and staff who were open to the idea of and have a need for an archive. However, it is not yet feasible to establish an archive due to circumstances and problems such as lack of motivation and financial challenges.
Thesis (Bachelor of Library and Information Science)
Keywords: Fe Del Mundo Medical Center; Archival materials -- Conservation and restoration; Archives